PENGEMBANGAN GAME EDUKASI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI KALIMAT MATEMATIKA DAN PERHITUNGAN KELAS 4 SD - Intania Riski Maharani; Bagus Ardi Saputro; Veryliana Purnamasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the low student activeness caused by the lack of use of educational learning media, so that students' ability to solve problems, especially in the material of mathematical sentences and calculations is less developed. This study aims to develop educational learning media based on Smart Apps Creator in the form of android applications on the material of mathematical sentences and calculations that are valid, practical, and effective for use by IVA grade students. The research method used is research and development with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of teachers and students of class IV A. The validation results showed that this media had a high level of validity, with a score of 93% from material experts and 98% from media experts. The practicality of the media was obtained from teacher responses of 94% and student responses of 88.4%. The implementation of this educational game media improves students' problem solving skills with an N-Gain value of 88.25%, which is included in the effective category. Thus, eduaction game media can be used as an alternative learning media in elementary schools